Improving Walkability of People with Reduced Mobility at An Intersection Using Microsimulation In VISSIM And SSAM - Elvira, Hurtado E. (2024)
In this research project, the evaluation of the accessibility and mobility difficulties faced by people with disabilities when circulating around a vehicular intersection is addressed. To carry out this evaluation, the Vissim and SSAM programs were used. The assessment of conflicts is carried out through the analysis of heat maps obtained with SSAM. In the context of this article, an analysis is carried out of the number of conflicts between vehicles on a road segment that is part of a traffic signalized intersection, characterized by the constant presence of congestion. Along this stretch, a decrease in lanes, variability in lane widths and lack of uniformity are observed, generating a point of congestion that gives rise to various types of vehicular conflicts. To carry out this evaluation, the micro simulation software VISSIM 8.0 was used, which models the real situation of the intersection. Two new scenarios are proposed, in which suggestions for geometric redesign are introduced in the infrastructure of the road section with the objective of analyzing the influence on the variability of the number of vehicular conflicts. The proposedmethodology consists of three fundamental stages: (i) obtaining the passage times of four types of vehicles that circulate in the area and the passagetimes of people with disabilities along the track, (ii) the modeling in the Vissim program and (iii) the implementation of the proposed improvements.